Panel comprising hardened inorganic foam and structural reinforcing elements, method for production thereof and use thereof
By attaching the structural design of hardened cementitious mortar to the hardened inorganic foam surface, the mechanical strength and recyclability of building heat insulation and fireproof boards are solved, and lightweight, high fire resistance and low environmental impact building panels are achieved.
Patent Information
- Application Number
- CN202380039220.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-20
AI Technical Summary
Existing building thermal insulation and fireproof boards have shortcomings in terms of mechanical strength, recyclability and environmental impact, especially the brittleness and high flammability of foamed cement materials, which are difficult to meet the needs of lightweight, fire resistance and ease of installation.
Hardened inorganic foam as the isolation layer and hardened mortar is securely attached to its surface as a structural reinforcement element, especially hardened cementitious mortar to improve mechanical strength while maintaining thermal insulation and fire resistance, and optimizing density and chemical composition To achieve a balance between lightweight and high density.
Lightweight building panels with high mechanical strength, good heat insulation and fire resistance are achieved, and are easy to install and recycle, reducing environmental impact.
Smart Images

Figure CN119173388A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a building panel comprising an insulating layer formed of a hardened inorganic foam and at least one structural reinforcement element firmly attached to at least one surface of the hardened inorganic foam. The panel of the invention can be used as a thermal and / or acoustic insulation board or as a cover board in construction and / or for fire protection. Background of the Invention
[0002] Building facades must be protected from environmental loads, such as wind and rain. Buildings must also be insulated to prevent unwanted flows of heat energy from the interior to the exterior of the building and vice versa. In addition, sound insulation and / or fire protection of buildings or between compartments within a building are becoming increasingly important. In particular, for the thermal insulation of buildings, it is known to perform external thermal insulation (EIFS), which consists in placing insulating panels and different layers of facing materials, such as mineral or organic gypsum, on the outer walls of the building, or to insulate from the inside (ITI), which consists in particular in placing insulating panels and different layers of facing materials on the inner walls of the building.
[0003] Rigid prefabricated insulation boards containing foamed synthetic organic materials, such as expanded polystyrene (EPS) foam boards, extruded expanded polystyrene (XPS) foam boards, polyurethane foam boards (PUR) and polyisocyanurates (PIR) are commonly used for the thermal insulation of building structures. Such materials have very low thermal conductivity, relatively high compressive strength and low density, usually not exceeding 150 g / l, which makes them very suitable for thermal insulation applications. The main disadvantage of foamed synthetic organic materials is their high flammability. Usually, additional fire protection structures must be applied, such as fire-resistant glass gauze or glass mats. In some countries, combustible "fire barrier strips" with a melting point of at least 1000°C must be added between adjacent insulation boards in the facade to meet fire protection requirements.
[0004] The sound insulation board may be made of, for example, mineral wool. The fire protection board may be made of, for example, a mineral wool-based sandwich board, or of a gypsum board, or of a cementitious mortar.
[0005] Foamed cementitious compositions are known and generally offer a combination of reduced weight and good thermal and / or acoustic insulation properties and excellent fire resistance. Foamed concrete, also known as cellular lightweight concrete (CLC), can be obtained by mixing a gas-generating foaming agent such as hydrogen peroxide or aluminum powder into the concrete paste or by separately generating an aqueous foam which is then mixed with the concrete paste.
[0006] Foamed cementitious compositions have good fire resistance, but they also have relatively low compressive and / or flexural strength due to the brittleness of the foamed material. Poor strength can cause problems during transportation, storage, handling and installation. To compensate for the disadvantages of poor mechanical properties, foamed cementitious boards can be used in combination with foamed synthetic organic boards (usually EPS boards) to provide lightweight insulating concrete (LWIC) systems.
[0007] WO 2021 / 023942 discloses an insulation board comprising an insulation layer formed of a cured inorganic foam and at least one open flexible reinforcing element. However, such composite materials are difficult to recycle.
[0008] EP 1088800 discloses an acoustic panel having a layer of foamed cementitious material and a backing layer fixed thereto, which backing layer may be made of paper, felt, glass fiber mat or mineral fiber board.
[0009] WO 2015 / 144796 discloses cement-based coating compositions suitable for passive fire protection.
[0010] The insulation board should be lightweight, have excellent fire protection properties and sufficient mechanical strength, in particular for compression and bending strength. The technical problem of the present invention is therefore to provide a thermal and / or acoustic insulation and / or fire protection board which is recyclable, has high fire resistance and is easy to install. Preferably, the thermal insulation board has a low environmental impact. SUMMARY OF THE INVENTION
[0011] The object of the present invention is to provide such a panel which simultaneously has insulating properties, in particular thermal and / or acoustic and / or fireproofing properties, has sufficient mechanical strength, and has good fire resistance properties. Preferably, the panel of the invention is also lightweight, ie has a low density.
[0012] Surprisingly, it has been found that a plate according to claim 1 is a solution to this object.
[0013] The core of the invention lies in the discovery that a sufficiently high mechanical strength of a panel comprising a hardened inorganic foam as an insulating layer can be achieved by firmly attaching at least one structural reinforcement element to the surface of said inorganic foam, wherein said at least one structural reinforcement element is a hardened mortar. The insulating properties, in particular the thermal and / or acoustic insulation properties, and the fire resistance are not impaired. A particularly suitable material for the structural reinforcement element is a hardened mortar, preferably a hardened cementitious mortar, in particular a hardened mortar having the same chemical composition as the hardened inorganic foam but having a higher density.
[0014] Further aspects of the invention are the subject matter of further independent claims. Preferred embodiments of the invention are the subject matter of the dependent claims. DETAILED DESCRIPTION
[0015] In a first aspect, the present invention relates to a panel comprising an insulating layer formed of a hardened inorganic foam and at least one structural reinforcement element firmly attached to at least one surface of the hardened inorganic foam, wherein the at least one structural reinforcement element is a hardened mortar, preferably a hardened cementitious mortar.
[0016] The panels herein may have any form or shape. According to a preferred embodiment, the panels may be in the form of a rectangular cuboid, in particular in the form of a rectangular plate. However, other shapes and forms, in particular irregular shapes, are also possible. It is particularly preferred that the panels of the invention are shaped in a regular manner so that they can completely cover a given surface with thin joints and without any overlap. The size of the panels of the invention is not particularly limited. However, a size suitable for the panels to be installed on the building is generally preferred.
[0017] The panel may be a prefabricated panel. The panel may also be manufactured on site, for example, it may be a formed-in-situ panel or a cast-in-situ panel.
[0018] The panel of the invention comprises an insulating layer. An insulating layer is a layer having insulating properties, in particular a layer having heat-insulating and / or sound-insulating and / or fire-proof properties. In other words, the insulating layer is preferably a heat-insulating and / or sound-insulating and / or fire-proof layer, in particular a heat-insulating layer. According to an embodiment, the thermal conductivity of the heat-insulating layer is between 0.02 and 0.15 W / m·K, preferably between 0.03 and 0.07 W / m·K. The thermal conductivity is measured according to standard DIN EN 12664:2001.
[0019] The insulating layer is formed by a hardened inorganic foam. In other words, the insulating layer consists of a hardened inorganic foam. The term "hardened inorganic foam" in this article refers to a material based on a cured inorganic binder and having a pore structure. Preferably, the pore structure is a closed-cell structure. However, it can also be an open-cell structure.
[0020] According to an embodiment, the density of the isolation layer is not greater than 500 g / l, preferably not greater than 350 g / l, more preferably not greater than 250 g / l, even more preferably not greater than 200 g / l, preferably in the range of 25-250 g / l, more preferably in the range of 35-150 g / l.
[0021] Throughout this text, when density is mentioned or density values are given, these densities are measured gravimetrically. The preferred method of measurement is as follows: a sample cube of dimensions 10×10×10 cm is first cut from the material and then dried in an oven at 70°C until the weight of the material remains constant. The weight of the sample cube is then measured and the density of the material (in g / l) is obtained by dividing the measured weight of the cube (in g) by 1 l.
[0022] In the context of the present invention, the term "low density" stands for a density of not more than 500 g / l.
[0023] According to an embodiment, in the panel of the invention, the density of at least one structural reinforcement element, in particular all structural reinforcement elements, is at least 1.5 times, preferably at least 2.5 times, the density of the insulation layer. For example, if the density of the insulation layer is 100 g / l, the density of at least one structural reinforcement element is at least 150 g / l, preferably at least 250 g / l.
[0024] It may also be preferred that in the panel of the invention the at least one structural reinforcement element has a density of at least 150 g / l, more preferably at least 250 g / l.
[0025] According to an embodiment, the total density of the panel of the invention is not higher than 500 g / l, in particular not higher than 300 g / l, preferably in the range between 110-500 g / l, more preferably between 160-250 g / l.
[0026] The mechanical strength of the panels and / or materials described in the present invention can be measured as the impact resistance of the cured material. The impact resistance can be measured according to the standards EN ISO 7892 and / or EOTA EAD 040083-00-0404 (2019). Another way to measure the mechanical strength is to measure the compressive strength, for example according to the standard DIN EN 826:2013. Impact resistance and compressive strength are related to each other. This means that a higher impact resistance is always associated with a higher compressive strength and vice versa.
[0027] According to an embodiment, the hardened inorganic foam of the present invention comprises:
[0028] a) at least one cured inorganic binder B,
[0029] b) at least one surfactant S and / or particles N, and
[0030] c) Optionally at least one synthetic organic polymer SP.
[0031] Preferably, at least one inorganic binder B is selected from cement, gypsum, lime, latent hydraulic binders, pozzolans and geopolymers. The cement may in particular be Portland cement as described in standard EN 197-1:20 18-11, calcium aluminate cement as described in standard EN 14647 and / or calcium sulphoaluminate cement. The term "gypsum" is intended to include various forms of CaSO 4 , especially CaSO 4 Anhydrite, CaSO 4 α- and β-hemihydrates and CaSO 4 dihydrate. The term "lime" is meant to include natural hydraulic lime, formula lime, hydraulic lime and air lime as described in standard EN459-1:2015. Pozzolans and latent hydraulic materials are preferably selected from clay, calcined clay (especially metakaolin), kiln dust, microsilica, fly ash, zeolite, rice husk ash, slag (especially blast furnace slag), burnt oil shale and natural pozzolans (such as pumice and volcanic ash). Geopolymers are aluminosilicate polymers. A specific example of a geopolymer is slag activated with waterglass.
[0032] Preferably, the at least one inorganic binder B is selected from Portland cement, calcium aluminate cement, calcium sulphoaluminate cement, latent hydraulic binder materials, pozzolanic binder materials, calcium sulfate and / or slaked lime. In particular, the at least one inorganic binder B is selected from Portland cement, calcium aluminate cement and / or calcium sulphoaluminate cement.
[0033] The term "Portland cement" as used herein refers in particular to the cement described in European Standard EN-197. Portland cement is mainly composed of tricalcium silicate (alite) (C 3 S) and dicalcium silicate (belite) (C 2 S) composition. Preferred Portland cements include types CEM I, CEM II, CEM III, CEM IV and CEM V of European standard EN 197-1:2018-11. However, all other Portland cements produced according to another standard, for example according to ASTM standards, British (BSI) standards, Indian standards or Chinese standards, are also suitable.
[0034] As used herein, the term "aluminate cement" is intended to include cement containing hydraulic calcium aluminate, preferably monocalcium aluminate CA (CaO·Al 2 O 3 ) as the main component (phase) of those cementitious materials. Depending on the type of aluminate cement, other calcium aluminates may also be present, such as CA 2 , C 3 A and C 12 A 7 The preferred aluminate cement also includes other ingredients, such as belite (C2 S), Alite (C 3 S), ferrite (C 2 F.C 2 AF, C 4 AF) and dolomite (C 5 S 2 $). Some aluminate cements also contain calcium carbonate.
[0035] The most preferred aluminate cements for use as the at least one inorganic binder B include calcium aluminate cements (CAC) which meet the requirements of standard EN 4647 ("Calcium aluminate cements"). Suitable calcium aluminate cements are commercially available from, for example, Imerys Aluminates and Royal White Cement.
[0036] The term "calcium sulphoaluminate cement (CSA)" is intended to include cements containing as the main constituent (phase) C 4 (A 3-x F x )3$ (4CaO· 3-x Al 2 O 3 · xFe 2 O 3 · CaSO 4 ) wherein the value of x is 0, 1, 2 or 3. Typically, calcium sulfoaluminate cements also include other ingredients such as aluminates (Ca, C 3 A.C 12 A 7 ), Belite (C 2 S), ferrite (C 2 F.C 2 AF, C 4 AF), ternesite (C 5 S 2 The preferred calcium sulfoaluminate cement used as at least one inorganic binder B contains 20-80w% of ye'elimite (C 4 A 3 $), 0-10w% calcium aluminate (CA), 0-70w% belite (C 2 S), 0-35w% ferrite, preferably tetracalcium aluminum ferrite (C 4 AF) and 0-20w% trihydrotalcite (C 5 S 2 $). Suitable calcium sulfoaluminate cements (CSA) are commercially available, for example from Heidelberg Cement AG, Vicat SA and Caltra BV.
[0037] The cured inorganic binder B is an inorganic binder B that has reacted, preferably substantially completely reacted, in a curing reaction in the presence of water. In particular, the curing reaction comprises the formation of a solid hydrate or a solid hydrate phase. The term "substantially completely reacted" refers to a substantially complete reaction at 25°C, 1023 mbar and 50% rh.
[0038] According to one or more embodiments, the weight ratio of the amount of at least one inorganic binder B to the amount of at least one synthetic organic polymer SP in the hardened inorganic foam is from 100:0 to 70:30, preferably from 100:0 to 80:20.
[0039] According to one or more embodiments, at least one synthetic organic polymer is present and the proportion of at least one synthetic organic polymer SP relative to the weight of at least one inorganic binder B in the hardened inorganic foam is 1-25w%, preferably 5-15w%, more preferably 8-12w%.
[0040] The at least one synthetic organic polymer SP can be used to improve the mechanical properties of the hardened inorganic foam, in particular the compressive strength and / or the flexural strength.
[0041] The type of synthetic organic polymer SP is not particularly limited. Suitable synthetic organic polymers include, for example, polyurethane polymers and homopolymers and copolymers obtained by free radical polymerization of one or more monomers selected from ethylene, propylene, butylene, isoprene, butadiene, styrene, acrylonitrile, (meth)acrylic acid, (meth)acrylates, vinyl esters, vinyl neodecanoate, vinyl alcohol and vinyl chloride. The term "(meth)acrylate" refers to acrylates and methacrylates, and the term "(meth)acrylics" refers to acrylics and methacrylics.
[0042] The term "polyurethane polymer" refers to polymers prepared by the so-called diisocyanate polyaddition process, including those polymers that are almost or completely free of urethane groups. Examples of suitable polyurethane polymers include polyether polyurethanes, polyester polyurethanes, polyether polyureas, polyureas, polyester polyureas, polyisocyanurates and polycarbodiimides.
[0043] According to one or more embodiments, the at least one synthetic organic polymer SP is a polyurethane polymer, preferably based on at least one polyisocyanate and at least one polyol and / or polyamine monomer.
[0044] Suitable polyisocyanates include monomeric polyisocyanates, as well as oligomers, polymers and derivatives of monomeric polyisocyanates, and mixtures thereof.
[0045] Suitable monomeric polyisocyanates for the polyurethane polymer include at least aromatic difunctional and trifunctional isocyanates, such as 2,4- and 2,6-toluene diisocyanate and mixtures of isomers thereof (TDI), 4,4'-, 2,4'- and 2,2'-diphenylmethane diisocyanate and mixtures of isomers thereof (MDI), 1,3- and 1,4-phenylene diisocyanate, 2,3,5,6-tetramethyl-1,4-diisocyanatobenzene, naphthalene-1,5-diisocyanate (NDI), 3,3'-dimethyl-4,4'-diisocyanatobiphenyl (TODI), dianisidine diisocyanate (DADI), 1,3,5-tris-(isocyanatomethyl)benzene, tris-(4-isocyanatophenyl)methane and tris-(4-isocyanatophenyl)phosphorothioate.
[0046] Other suitable monomeric polyisocyanates for use in the polyurethane polymers include aliphatic difunctional and trifunctional isocyanates such as 1,4-tetramethylene diisocyanate, 2-methylpentamethylene-1,5-diisocyanate, 1,6-hexamethylene diisocyanate (HDI), 2,2,4- and 2,4,4-trimethyl-1,6-hexamethylene diisocyanate (TMDI), 1,10-decamethylene diisocyanate, 1,12-dodecamethylene diisocyanate, lysine- and lysine ester diisocyanates, cyclohexane-1,3- and -1,4-diisocyanate, 1-methyl-2,4- and -2,6-diisocyanatocyclohexane and mixtures of their isomers (HTDI or H6TDI), 1-isocyanato-3,3,5-trimethyl-5-isocyanate methyl-cyclohexane (=isophorone diisocyanate or IPDI), perhydro-2,4'- and -4,4'-diphenylmethane diisocyanate (HMDI or H12MDI), 1,4-isocyanato-2,2,6-trimethylcyclohexane (TMCDI), 1,3- and 1,4-bis-(isocyanatomethyl)cyclohexane, m- and p-xylylene diisocyanate (m- and p-XDI), m- and p-tetramethyl-1,3- and -1,4-xylylene diisocyanate (m- and p-TMXDI), bis-(1-isocyanato-1-methyl-ethyl)naphthalene, dimer and trimer fatty acid isocyanates such as 3,6-bis-(9-isocyanatononyl)-4,5-di-(1-heptenyl)cyclohexene (dimer diisocyanate) and α, α, α', α',α'', α''-Hexamethyl-1,3,5-mesitylene triisocyanate.
[0047] Particularly suitable polyols for use in the polyurethane polymers include polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylate polyols and hydrocarbon polyols such as polybutadiene polyols, polyhydroxy-functional fats and oils and polyhydroxy-functional acrylonitrile-butadiene copolymers.
[0048] Particularly suitable polyether polyols include polyoxyalkylene diols and / or polyoxyalkylene triols, in particular the polymerization products of ethylene oxide or 1,2-propylene oxide or 1,2- or 2,3-butylene oxide or oxetane or tetrahydrofuran or mixtures thereof, which can be polymerized using starter molecules having two or three, in particular one, active hydrogen, such as water, ammonia or compounds having several OH or NH groups, such as 1,2-ethylene oxide or 1,2- or 2,3-butylene oxide or oxetane or tetrahydrofuran or mixtures thereof. diol, 1,2- or 1,3-propylene glycol, neopentyl glycol, diethylene glycol, triethylene glycol, isomeric dipropylene glycol or tripropylene glycol, isomeric butanediols, pentanediol, hexanediol, heptanediol, octanediol, nonanediol, decanediol, undecanediol, 1,3- or 1,4-cyclohexanedimethanol, bisphenol A, hydrogenated bisphenol A, 1,1,1-trimethylolethane, 1,1,1-trimethylolpropane, glycerol or aniline, or mixtures thereof.
[0049] Suitable polyester polyols include liquid polyester polyols as well as amorphous, partially crystalline and crystalline polyester polyols which are solid at a temperature of 25° C. These can be prepared by reacting diols and triols, preferably diols such as 1,2-ethanediol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, dipropylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dodecanediol, dimer fatty alcohols, neopentyl glycol, glycerol, 1,1,1-trimethylolpropane or mixtures of the aforementioned alcohols with an organic diol. Carboxylic acids or tricarboxylic acids, preferably dicarboxylic acids or their anhydrides or esters, such as succinic acid, glutaric acid, 3,3-dimethylglutaric acid, adipic acid, suberic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, azelaic acid, maleic acid, fumaric acid, phthalic acid, dimer fatty acids, isophthalic acid, terephthalic acid and hexahydrophthalic acid, or mixtures of the aforementioned acids, and polyester polyols made from lactones such as ε-caprolactone, also known as polycaprolactones, for example.
[0050] Suitable polyamine monomers are compounds having two or more isocyanate-reactive amine groups. Examples of polyamine monomers that can be used include diethyltoluenediamine, methylbis(methylthio)phenylenediamine, adipic acid dihydrazide, ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, dipropylenetriamine, hexamethylenediamine, hydrazine, isophoronediamine, N-(2-aminoethyl)-2-aminoethanol, polyoxyalkyleneamines, adducts of salts of 2-acrylamido-2-methylpropane-1-sulfonic acid (AMPS) and ethylenediamine, adducts of salts of (meth)acrylic acid and ethylenediamine, adducts of 1,3-propanesulfone and ethylenediamine, or any desired combination of these polyamines.
[0051] According to one or more preferred embodiments, the at least one synthetic organic polymer SP is selected from polyacrylates, styrene-acrylate copolymers, polyvinyl esters, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, styrene-butadiene copolymers, vinyl acetate-vinyl neodecanoate (VeoVa) copolymers and polyurethane polymers.
[0052] According to one or more preferred embodiments, the at least one synthetic organic polymer SP comprises at least one ethylene-vinyl acetate copolymer and / or at least one terpolymer of ethylene, vinyl acetate and vinyl ester monomers.
[0053] Particularly suitable ethylene-vinyl acetate copolymers for use as at least one synthetic organic polymer SP have a content of structural units derived from vinyl acetate of not more than 40% by weight, preferably not more than 30% by weight, more preferably not more than 20% by weight, still more preferably not more than 15% by weight, based on the weight of the copolymer.
[0054] According to an embodiment, at least one synthetic organic polymer SP is present in the form of an aqueous polymer dispersion and / or in the form of a redispersible polymer powder. The synthetic organic polymer SP can be mixed with the inorganic binder B using any conventional mixing technique. The synthetic organic polymer can also be added to the cement paste together with the aqueous foam, however, this is less preferred. The aqueous polymer dispersion of at least one synthetic organic polymer SP can be prepared, for example, by free radical polymerization using bulk, solution, suspension or emulsion polymerization techniques (which are well known to those skilled in the art), or by mixing a redispersed polymer powder with water. Aqueous polymer dispersions containing two or more different synthetic organic polymers SP can be easily prepared by using a mixture of commercially available aqueous polymer dispersions and / or redispersible polymers.
[0055] The synthetic organic polymer SP may additionally be stabilized. Preferably, the synthetic organic polymer SP is stabilized with polyvinyl alcohol (PVA).
[0056] According to one or more embodiments, the hardened inorganic foam further comprises at least one surfactant S. The term "surfactant" herein refers to a substance that reduces surface tension, which is generally an organic compound containing hydrophobic and hydrophilic groups.
[0057] Surfactants can be used to stabilize the foam structure during the preparation of hardened inorganic foams. Surfactants S can also form part of the aqueous foam.
[0058] According to one or more embodiments, the proportion of at least one surfactant S is 0.1-25w%, preferably 1-15w%, more preferably 5-12w%, relative to the total dry weight of the hardened inorganic foam.
[0059] Surfactants are well known to those skilled in the art and are summarized in, for example, "Surfactants and Polymers in Aqueous Solutions" (Wiley-VCH, K. Holmberg et al., 2nd edition, 2007). Suitable surfactants include at least nonionic surfactants, cationic surfactants, anionic surfactants and amphoteric surfactants. Amphoteric (zwitterionic) surfactants have a cationic and anionic center attached to the same molecule.
[0060] The use of nonionic surfactants may be particularly advantageous since they have a low tendency to be absorbed by the cement phase. However, cationic, anionic or amphoteric (zwitterionic) surfactants may also be used.
[0061] In the context of the present invention, suitable surfactants include lipids, such as cholate, glycocholate, fatty acid salts, glycerides, glycolipids and phospholipids. These can be derived from natural sources or can be produced synthetically. In certain embodiments, nonionic lipids are preferred.
[0062] Suitable anionic surfactants include compounds containing carboxylate, sulfate, phosphate or sulfonate groups, such as alkyl sulfonates, alkyl ether carboxylates, alkyl sulfates, alkyl ether sulfates, fatty alcohol sulfates, alkyl sulfosuccinates, alkylphenol ethoxylates, olefin sulfonates, alkyl phosphates, alkyl ether phosphonates, lauryl ether sulfonates, naphthalene sulfonates and alkylbenzene sulfonates.
[0063] Suitable nonionic surfactants include, in particular, fatty acid alkoxylates, alkoxylated alcohols, in particular fatty acid alcohol alkoxylates and alkoxylates of glycerol and pentaerythritol, alkylphenol alkoxylates, alkoxylated polysaccharides, alkoxylated polycondensates, fatty acid amide alkoxylates, ethanolamides, fatty acid esters, in particular fatty acid esters of methanol, sorbitan, glycerol or pentaerythritol, alkoxylated alkylamines with an alkyl group consisting of 6 to 20 carbon atoms, alkyl glycosides, alkyl glucamides, esters of fatty acids and sugars, polysiloxanes and alkoxylated sorbitan, copolymers of ethylene oxide and propylene oxide, hydrophobized starches, hydrophobized celluloses, proteins or silicone-based surfactants. Preferred alkoxylates in this context are in particular ethoxylates.
[0064] In particular, the use of protein surfactants results in a mixture that is sufficiently stable and does not require any other additives to solidify into a hardened inorganic foam having a low density.
[0065] Suitable cationic surfactants contain in particular an ammonium group or a quaternary nitrogen atom and have at least one long-chain alkyl group. Examples of suitable cationic surfactants are quaternary ammonium compounds having at least one alkyl group, phosphonium compounds such as tetraalkylammonium salts, imidazolines such as N,N-dialkylimidazoline compounds, dimethyldistearylammonium compounds, N-alkylpyridinium compounds, ammonium chlorides and amine N-oxides. For example, the cationic surfactant can be selected from tetradecyltrimethylammonium bromide (TTAB), hexadecyltrimethylammonium bromide (CTAB) and dodecyltrimethylammonium bromide (DTAB).
[0066] According to one or more embodiments, at least one surfactant S comprises at least one Gemini surfactant or consists of at least one Gemini surfactant. Gemini surfactants contain two hydrophilic head groups and two hydrophobic tails, which are separated by a spacer at or near the head group. When the two hydrophobic tails are identical and the hydrophilic groups are identical, the Gemini surfactant is said to have a symmetrical structure. The substituents in the Gemini surfactants are primarily responsible for the behavior of these compounds in solution and their potential applications. In particular, Gemini surfactants can contain quaternary nitrogen atoms, which are usually present in acyclic form. However, there are also Gemini surfactants containing nitrogen in saturated and unsaturated rings. The spacer can be rigid or flexible, tending to be hydrophobic or hydrophilic. The special properties of Gemini surfactants can be influenced by optimizing the hydrophilic-lipophilic balance (HLB value). This can be achieved, for example, by introducing balanced polar or hydrophobic groups in the head group, tail or spacer. Examples of preferred Gemini surfactants are particularly alkoxylated acetyl glycols or Gemini surfactants as described in EP 0 884 298.
[0067] According to one or more further embodiments, the at least one surfactant S comprises an anionic surfactant and / or a nonionic surfactant, preferably a mixture of anionic surfactants and / or nonionic surfactants.
[0068] According to one or more other embodiments, at least one surfactant S is an amphoteric surfactant, preferably selected from aminocarboxylic acids and betaines, especially fatty acid amide alkyl betaines, in particular cocamidopropyl betaine. Betaine is a neutral compound with a positively charged cationic functional group, such as a quaternary ammonium or phosphonium ion, without a hydrogen atom, with a negatively charged functional group, such as a carboxylic acid group, not adjacent to the cationic position. Therefore, betaine is a specific type of zwitterion. These types of surfactants are very useful in the context of the present invention because they are highly compatible with other ingredients that are usually present in the foaming inorganic material.
[0069] According to an embodiment, particles N are present in the composition of the invention.
[0070] The particles N of the present invention preferably have a particle size of 10 nm to 500 μm, preferably 20 nm to 300 μm, more preferably 25 nm to 150 μm, still more preferably 30 nm to 100 μm, especially 30 nm to 1 μm. The particle size can be determined by laser diffraction as described in ISO 13320:2009. In particular, a Mastersizer 2000 instrument with a Hydro 2000G dispersion unit and Mastersizer 2000 software from Malvern Instruments GmbH (Germany) is used. For example, isopropanol is suitable as a measuring medium. Preferably, the particle size of non-spherical or irregular particles is represented by the equivalent spherical diameter of a sphere of equal volume. In the present invention, whenever a particle size range is given, the lower limit of the range represents the D10 value, while the upper limit of the particle size range given herein represents the D90 value of the corresponding particle size distribution.
[0071] According to some embodiments, the particles N of the present invention are nanoparticles. This means that the particles N have a particle size in the nanometer range, in particular a particle size D50.
[0072] In particular, the particles N are selected from inorganic particles, especially pure and mixed metal oxides, hydroxides, carbides, nitrides, phosphates, carbonates, silicates, sulfates. According to an embodiment, the particles N are selected from the following particles: clay, talc, silicon dioxide, calcium carbonate, ferrite, gibbsite, titanium oxide, zinc oxide, aluminum oxide, magnesium oxide, zirconium oxide, tin oxide, cerium oxide, spinel, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, silicon carbide, boron carbide, silicon nitride, boron nitride, calcium phosphate, nickel carbonate, calcium carbonate, magnesium carbonate, silica fume, fly ash, quartz, ground glass, slag, calcium silicate, mullite, cordierite, zeolite, diatomaceous earth, cement, calcium sulfate and / or carbon black particles. In particular, the particles are silica particles.
[0073] According to another preferred embodiment, the particles are selected from organic particles, in particular polymer particles, in particular polystyrene particles and / or poly(methyl methacrylate) particles.
[0074] The proportion of particles N, if present, is in particular 1 to 50% by volume, in particular 2 to 20% by volume, especially 3 to 10% by volume, relative to the total volume of the hardened inorganic foam.
[0075] In this context, aqueous foams are materials comprising a gas phase dispersed in water. The gas may be any gas, for example air, nitrogen, carbon dioxide, a noble gas or a mixture thereof, preferably air. The aqueous foam may additionally comprise other ingredients, in particular at least one surfactant S as described above. Methods for producing aqueous foams are known per se to the person skilled in the art. For example, a foaming device from the company Gertec may be used.
[0076] The aqueous foam is preferably prepared by mechanical frothing of the aqueous mixture in the presence of a gas, in particular air, nitrogen and / or carbon dioxide and / or a noble gas. Mechanical frothing is a process in which gas bubbles are introduced into the water of the aqueous foam by mixing gas with water without any chemical reaction producing the gas.
[0077] According to one or more embodiments, the aqueous foam is obtained by mechanically frothing the aqueous mixture with a gas, preferably with air.
[0078] According to an embodiment, the hardened inorganic foam of the present invention is obtained in a process comprising the following steps:
[0079] Providing a wet mixture, the wet mixture comprising: (i) at least one inorganic binder B, (ii) optionally, 1-25w%, preferably 5-15w%, more preferably 8-12w% of at least one synthetic organic polymer SP, relative to the dry weight of the inorganic binder B, (iii) optionally, 0.01-10w% of a superplasticizer for the inorganic binder B, relative to the dry weight of the inorganic binder B, and (iv) water, in an amount such that the weight ratio of water to inorganic binder B is 0.2-0.6;
[0080] An aqueous foam is provided, comprising: (i) water, and (ii) 0.1% to 25% by weight, preferably 1% to 15% by weight, more preferably 1% to 10% by weight of a surfactant S and / or particles N, relative to the total weight of the aqueous foam,
[0081] mixing the wet mixture with the aqueous foam of steps a) and b), and
[0082] The mixture obtained in step c) is allowed to harden.
[0083] According to an embodiment, the hardened inorganic foam of the present invention is obtained in a process comprising the following steps:
[0084] Providing a wet mixture, the wet mixture comprising: (i) at least one inorganic binder B, (ii) optionally, 1-25w%, preferably 5-15w%, more preferably 8-12w% of at least one synthetic organic polymer SP, relative to the dry weight of the inorganic binder B, (iii) optionally, 0.01-10w% of a superplasticizer for the inorganic binder B, relative to the dry weight of the inorganic binder B, and (iv) water, in an amount such that the weight ratio of water to inorganic binder B is 0.2-0.6;
[0085] An aqueous foam is provided, comprising: (i) water, and (ii) 1-50% by volume, particularly 2-20% by volume, especially 3-10% by volume of particles N, relative to the total volume of the aqueous foam,
[0086] mixing the wet mixture with the aqueous foam of steps a) and b), and
[0087] The mixture obtained in step c) is allowed to harden.
[0088] In such an embodiment, the weight ratio of a) and b) depends on the desired density. Lower densities are achieved by higher dosages of b). According to an embodiment, the weight ratio of a) and b) is from 10:1 to 1:10.
[0089] According to a further embodiment, the hardened inorganic foam of the invention is obtained in a process consisting of the following steps:
[0090] providing a wet mixture comprising: (i) at least one cement, (ii) about 10% by weight of at least one synthetic organic polymer SP, relative to the dry weight of the cement, (iii) about 0.2% by weight of a superplasticizer for the cement, relative to the dry weight of the cement, and (iv) water in an amount such that the weight ratio of water:cement is 0.4;
[0091] An aqueous foam is provided, the aqueous foam comprising: (i) water, and (ii) about 3 wt % of a surfactant S relative to the total weight of the aqueous foam,
[0092] mixing the wet mixture with the aqueous foam of steps a) and b), and
[0093] The mixture obtained in step c) is allowed to harden.
[0094] According to an embodiment, the weight ratio of a) to b) is from 10:1 to 1:10.
[0095] According to a further embodiment, the hardened inorganic foam of the invention is obtained in a process comprising the following steps:
[0096] A suspension is provided, the suspension comprising: (i) at least one inorganic binder B, (ii) at least one surfactant S and / or particles N,
[0097] Optionally, 1-25w%, preferably 5-15w%, more preferably 8-12w% of at least one synthetic organic polymer SP, relative to the dry weight of the inorganic binder B,
[0098] Optional other additives, and
[0099] Water, in an amount such that the weight ratio of water to the inorganic binder B is 0.2-0.6,
[0100] foaming the suspension provided in step a), and
[0101] The foamed mixture obtained in step b) is allowed to harden.
[0102] The foaming can be carried out by any method known to those skilled in the art. In particular, the foaming can be carried out by chemical foaming, mechanical foaming and / or physical foaming methods.
[0103] The hardened inorganic foam of the present invention may additionally contain other additives commonly used in the concrete or mortar industry. In particular, the inorganic foam of the present invention may include aggregates, fillers, superplasticizers, shrinkage reducers, air entrainers, deaerators, rheology modifiers, accelerators, retarders, waterproofing agents, strength enhancing additives, fibers, defoamers, redispersible polymer powders, chromate reducing agents, pigments, corrosion inhibitors, alkali-aggregate reaction inhibitors, antifreeze agents, hydrophobic agents and / or biocides.
[0104] The hardening of the inorganic foam usually occurs when the inorganic binder B is in contact with water and / or when the inorganic binder is reacted at a pressure of 5-50° C. and 1 atm. Hardening at higher temperatures and / or higher pressures is not preferred in this article. When mechanical strength, especially impact resistance, bending strength and / or compressive strength no longer increase significantly over time, a hardened inorganic foam is obtained. Usually, a hardened inorganic foam is obtained after hardening for 28 days at 20° C. and 1 atm. It is beneficial to cover the inorganic foam or panel during the hardening process. Covering prevents rapid evaporation of water and can lead to higher compressive strength. The hardened inorganic foam or panel of the present invention can be dried at an elevated temperature, for example at 40-90° C.
[0105] The flexural strength can be measured according to DIN EN 1015-11. The compressive strength can be measured according to DIN EN 826:2013. The impact resistance can be measured according to standard EN ISO 7892 and / or EOTA EAD 040083-00-0404 (2019).
[0106] The method for obtaining the hardened inorganic foam according to the invention is known to the person skilled in the art and is described, for example, in WO 2019 / 038105.
[0107] According to an embodiment, the method for producing a hardened inorganic foam comprises the following steps:
[0108] (i) providing a dry mixture Md1 comprising at least one inorganic binder B and optionally further additives as described above, (ii) optionally mixing the dry mixture Md1 with at least one synthetic organic polymer SP, (iii) mixing the mixture obtained in (ii) with an aqueous foam, wherein the aqueous foam comprises at least one surfactant S, to obtain a wet mixture Mw1, (iv) optionally subjecting the wet mixture Mw1 to any desired form and shape, (v) hardening the wet mixture Mw1 at 5-50° C. and a pressure of 1 atm.
[0109] The mixture of aqueous foam and Md1 and optionally SP is preferably mixed with one another under overpressure conditions. Preferably, it is under an overpressure of 1 to 15 bar, in particular 2 to 5 bar, relative to the ambient air pressure. This allows the density of the hardened inorganic foam to be easily adjusted within a wide range.
[0110] Most preferably, mixing is performed using a static mixer, wherein preferably the aqueous foam and the mixture of Md1 and optionally SP are driven through the static mixer by pressurized air. Preferably, the pressurized air has a pressure of 1-15 bar, in particular 6-10 bar, higher than the ambient air pressure. Thus, a stable foam can be obtained in a reliable manner. The aqueous foam can be mixed with the slurry in batches or continuously.
[0111] The weight ratio of water to the at least one inorganic binder B in the wet mixture Mw1 is preferably 0.2-0.7, more preferably 0.25-0.5, even more preferably 0.3-0.4.
[0112] According to an alternative embodiment, the method for producing a hardened inorganic foam comprises the following steps: (i) providing a dry mixture Md1 comprising at least one inorganic binder B and optionally other additives as described above, (ii) optionally mixing the dry mixture Md1 of step (i) with at least one synthetic organic polymer SP and with water to prepare a wet mixture Mw, (iii) mixing the mixture obtained in (ii) with an aqueous foam, wherein the aqueous foam comprises at least one surfactant S, to obtain a wet mixture Mw1, (iv) optionally causing the wet mixture Mw1 to be in any desired form and shape, (v) hardening the wet mixture Mw1 at 5-50°C and a pressure of 1 atm.
[0113] The aqueous foam and the wet mixture Mw are preferably mixed with one another under overpressure conditions. Preferably, under an overpressure of 1 to 15 bar, in particular 2 to 5 bar, relative to the ambient air pressure. This makes it easy to adjust the density of the hardened inorganic foam within a wide range.
[0114] Most preferably, mixing is performed using a static mixer, wherein preferably the aqueous foam and the wet mixture Mw are driven through the static mixer by pressurized air. Preferably, the pressurized air has a pressure of 1 to 15 bar, in particular 2 to 5 bar, higher than the ambient air pressure. Thus, a stable foam can be obtained in a reliable manner. The aqueous foam can be mixed with the slurry in batches or continuously.
[0115] The weight ratio of water to the at least one inorganic binder B in the wet mixture Mw is preferably from 0.2 to 0.7, more preferably from 0.25 to 0.5, even more preferably from 0.3 to 0.4.
[0116] According to an alternative embodiment, the method for producing a hardened inorganic foam comprises the following steps: (i) providing a dry mixture Md1 comprising at least one inorganic binder B and optionally other additives as described above, (ii) mixing at least one surfactant S, water and optionally at least one synthetic organic polymer SP with the dry mixture Md1 to prepare a wet mixture Mw1, (iii) foaming the wet mixture Mw1 obtained in (ii), (iv) optionally subjecting the foamed wet mixture Mw1 to any desired form and shape, and (v) hardening the foamed wet mixture Mw1 at 5-50°C and a pressure of 1 atm.
[0117] The weight ratio of water to the at least one inorganic binder B in the wet mixture Mw1 is preferably 0.2-0.7, more preferably 0.25-0.5, even more preferably 0.3-0.4.
[0118] Therefore, the hardened inorganic foam of the present invention is obtained by providing a dry mix Md1 comprising at least one inorganic binder B and optionally other additives as described above, preparing a wet mix Mw1 from the dry mix Md1 by adding an aqueous foam, wherein the aqueous foam comprises at least one surfactant S and optionally at least one synthetic organic polymer SP, and hardening the wet mix Mw1.
[0119] According to an embodiment, the density of the hardened inorganic foam is not more than 500 g / l, preferably not more than 350 g / l, more preferably not more than 250 g / l, even more preferably not more than 200 g / l, such as 25-250 g / l, preferably 35-150 g / l.
[0120] According to an embodiment, the hardened inorganic foam has a thermal conductivity of 0.02-0.15 W / m·K, preferably 0.03-0.07 W / m·K. The thermal conductivity is measured as described in standard DIN EN 12664:2001.
[0121] The panel according to the invention comprises at least one structural reinforcement element which is firmly attached to at least one surface of the hardened inorganic foam and which is a hardened mortar, preferably a hardened cementitious mortar.
[0122] In particular, at least one structural reinforcement element forms the outer surface of the panel of the invention.
[0123] Firmly connected means that the structural reinforcement element cannot be easily removed from the surface of the hardened inorganic foam, preferably, the structural reinforcement element cannot be removed from the surface without damaging the hardened inorganic foam. In other words, preferably, the pull-off strength of at least one structural reinforcement element from the surface is higher than the tensile strength of the hardened inorganic foam.
[0124] Very preferably, at least one structural reinforcement element completely covers at least one surface of the hardened inorganic foam without any overlap. Panels with such a construction can be conveniently used to cover surfaces, such as the exterior of a building, by placing them adjacent to each other. However, at least one structural reinforcement element can also cover only a portion of one surface of the hardened inorganic foam. For example, a structural reinforcement element can cover half of one surface of the insulation layer, while the other half of the surface of the insulation layer is covered by an adjacent structural reinforcement element. According to some embodiments, a portion (e.g., half) of a structural reinforcement element covers a portion (e.g., half) of the surface of the insulation layer, while another portion (e.g., another half) of the same structural reinforcement element covers a portion (e.g., half) of another adjacent insulation layer. By repeating this construction, for example, the exterior of a building can be covered.
[0125] Particularly preferably, two or more surfaces, in particular two surfaces, of the hardened inorganic foam are completely covered by the structural reinforcement element. Thus, according to an embodiment, the panel according to the invention is characterized in that the first structural reinforcement element is firmly attached to the first surface of the insulating layer and the second reinforcement element is firmly attached to the second surface of the insulating layer. The first structural reinforcement element and the second structural reinforcement element may have the same chemical composition and density or may have different chemical compositions and / or densities. Particularly preferably, the first surface and the second surface of the insulating layer are opposite surfaces of the insulating layer.
[0126] According to a particularly preferred embodiment, the panel of the present invention comprises or consists of a first structural reinforcement element forming a first outer surface of the panel, an insulation layer formed by hardened inorganic foam and a second structural reinforcement element forming a second outer surface of the panel, the first structural reinforcement element and the second structural reinforcement element being arranged on opposite surfaces of the insulation layer.
[0127] The structural reinforcement element is a hardened mortar, preferably a hardened cementitious mortar. In particular, the hardened mortar of the present invention has almost the same chemical composition or substantially the same chemical composition as the hardened inorganic foam, but has a higher density. In this regard, the terms "almost the same" and "almost the same" mean that 80% by weight, preferably 90% by weight of the composition is chemically the same. Therefore, according to an embodiment, the insulating layer formed by the hardened inorganic foam and each structural reinforcement element are almost the same in chemical composition or have substantially the same chemical composition, and each structural reinforcement element has a higher density than the insulating layer.
[0128] Depending on the density of the hardened inorganic foam, the density of the hardened mortar may be not less than 200 g / l, preferably not less than 250 g / l, more preferably not less than 500 g / l, even more preferably not less than 1000 g / l, especially not less than 1500 g / l or not less than 2000 g / l.
[0129] According to an embodiment, the density of the structural reinforcement element as hardened mortar is at least 1.5 times higher, preferably at least 2 times higher, in particular at least 5 times higher, compared to the density of the hardened inorganic foam.
[0130] Preferred hardened mortars according to the invention are obtained from (in each case relative to the total dry weight of the composition):
[0131] 10-90w%, preferably 15-65w%, more preferably 30-55w% of at least one inorganic binder B,
[0132] 0-80w%, preferably 25-75w%, more preferably 35-60w% of aggregate, especially sand,
[0133] 0.01-10w% of other additives, and
[0134] water.
[0135] The amount of water used is sufficient to harden the at least one inorganic binder B and provide the desired workability for the dry mix of the mortar, especially cementitious mortar. Preferably, the amount of water used is such that the weight ratio of water to powder is 0.3-1.0, more preferably 0.5-0.8.
[0136] The at least one inorganic binder B is as defined above.
[0137] The other additives are selected from plasticizers, superplasticizers, rheology modifiers, accelerators, retarders, air entraining agents, deaerators, corrosion inhibitors, fibers, redispersible polymer powders, shrinkage reducers, pigments, strength enhancing additives, water repellents, alkali-aggregate reaction inhibitors, chromate reducing agents, defoamers, steel passivators, antifreeze agents and / or biocides.
[0138] Aggregate can be any material that does not react in the hydration reaction of the binder. Aggregate can be any aggregate commonly used in building materials. Typical aggregates are, for example, rock, crushed stone, gravel, sand (especially quartz sand, river sand and / or machine-made sand), recycled concrete, glass, expanded glass, hollow glass beads, glass ceramics, volcanic rock, pumice, perlite, vermiculite, quarry waste, raw, fired or fused soil or clay, porcelain, electrofused or sintered abrasives, fired carriers, silica xerogels. Aggregate can also be fine aggregate or filler, such as ground limestone, ground dolomite and / or ground alumina. Aggregate that can be used in the present invention can have any shape and size that this aggregate is usually encountered. Particularly preferred aggregate is sand. Sand is a naturally occurring granular material composed of finely crushed rock or mineral particles. It can be obtained in various forms and sizes. Examples of suitable sand are quartz sand, limestone sand, river sand or crushed aggregate. Suitable sands are described, for example, in standards ASTM C778 or EN 196-1.
[0139] According to an embodiment, the aggregate can also be one or more of the following (i)-(v): (i) a material of biological origin, preferably of plant origin, more preferably of plant origin consisting essentially of cellulose and / or lignin, in particular a material of biological origin selected from the group comprising or consisting of hemp, flax, cereal straw, oats, rice, rape, corn, sorghum, flax, miscanthus, rice husk, sugar cane, sunflower, kenaf, coconut, olive pits, bamboo, wood or mixtures thereof. According to an embodiment, the material of biological origin of plant origin has a defined form, which is preferably selected from fibers, fibrils, dust, powder, shavings, pith, in particular pith of sunflower, corn, rape and mixtures thereof. (ii) a synthetic non-mineral material, preferably selected from thermoplastics, thermosetting plastics, elastomers, rubber, textile fibers, plastic materials reinforced with glass or carbon fibers. The synthetic non-mineral material can be filled or unfilled. (iii) Aggregates of inorganic nature from the dismantling of civil engineering or building structures, preferably selected from the group comprising or consisting of waste concrete, mortar, bricks, natural stone, asphalt, tiles, tiles, aerated concrete, clinker, waste metal. (iv) Aggregates of organic nature from recycling of industrial products, in particular difficult to recycle composite materials, especially recycled insulation materials. Particularly preferred examples are polystyrene, polyurethane, phenolic resins, wood insulation materials and mixtures thereof.
[0140] (v) Non-hazardous particulate materials normally used in landfills, such as spent foundry sand, catalyst carriers, carriers from Bayer process descaling treatments, clinker aggregates, fill from excavation sludge treatment, sewage sludge, slurries, waste paper, waste paper incineration ash, household waste incineration ash.
[0141] Most preferably, the aggregate is in particulate form.
[0142] It is important in this context that the hardened mortar, especially the hardened cementitious mortar, forming the structural reinforcement layer has a mechanical strength high enough to resist external loads. For example, according to EOTA EAD 040083-00-0404 (2019), the impact resistance classification of the mortar should be Class I or II. For example, the compressive strength of the mortar should be not less than 70 kPa, preferably not less than 100 kPa, and more preferably not less than 300 kPa.
[0143] The flexural strength can be measured according to DIN EN 1015-11 and the compressive strength can be measured according to DIN EN 826: 2013. The impact resistance can be measured according to standard EN ISO 7892 and / or EOTA EAD 040083-00-0404 (2019).
[0144] Thus, according to an embodiment, the panel of the invention is characterized in that the reinforcing element is a hardened cementitious mortar obtained from (in each case relative to the total dry weight of the composition):
[0145] 10-90w%, preferably 15-65w%, more preferably 30-55w% of at least one inorganic binder B,
[0146] 0-80w%, preferably 25-75w%, more preferably 35-60w% of aggregate, especially sand,
[0147] 0.01-10w% of other additives, and
[0148] water,
[0149] And has an impact resistance classified as Class I or II according to EOTA EAD 040083-00-0404 (2019). In an alternative embodiment, the mortar has a compressive strength of not less than 70 kPa, preferably not less than 100 kPa, more preferably not less than 300 kPa.
[0150] According to a particularly preferred embodiment of the present invention, the reinforcing element is a hardened cementitious mortar having the same chemical composition as the hardened inorganic foam forming the insulating layer, wherein the hardened cementitious mortar has a higher density than the hardened inorganic foam. For example, the density of the hardened inorganic foam forming the insulating layer does not exceed 500 g / l, preferably does not exceed 350 g / l, more preferably does not exceed 250 g / l, even more preferably does not exceed 200 g / l, for example 25-250 g / l, preferably 35-150 g / l, and the density of the structural reinforcing element as hardened mortar is at least 1.5 times higher, preferably at least 2 times higher, in particular at least 5 times higher than the density of the hardened inorganic foam.
[0151] The different densities of the hardened cementitious mortar forming the reinforcing layer and the hardened inorganic foam forming the insulating layer can be achieved, for example, by mixing a) an aqueous slurry comprising at least one inorganic binder B, optionally at least one synthetic organic polymer SP and water, and b) an aqueous foam comprising water and a surfactant S and / or particles N in different weight ratios.
[0152] A higher weight ratio of a) to b) will result in a higher density, while a lower weight ratio will result in a lower density.
[0153] These embodiments offer the advantages of a particularly simple production process and improved recyclability.
[0154] The hardened cementitious mortar of the present invention is obtained by providing a dry mix Md2 mixture comprising at least one inorganic binder B, other additives and optionally aggregates as described above, preparing a wet mix Mw2 from the dry mix Md2 by adding water, and hardening the wet mix Mw2.
[0155] According to some particularly useful embodiments, the compositions of dry blend Md1 and dry blend Md2 as described above have the same composition.
[0156] According to an embodiment, the mortar, preferably cementitious mortar, used as the structural reinforcement element of the present invention is in the form of a flat layer or a flat sheet. In addition, the insulating layer can be in the form of a flat layer or a flat sheet. In some embodiments, the mortar, preferably cementitious mortar, used as the structural reinforcement element of the present invention is in the form of a flat layer or a flat sheet, and covers the insulating layer, preferably one surface of the flat sheet of the insulating layer, and has the same size as the surface of the insulating layer. In other embodiments, the mortar (preferably cementitious mortar) used as the structural reinforcement element covers two or more surfaces of the insulating layer, preferably two surfaces. The mortar (preferably cementitious mortar) can be in the form of several flat layers or flat sheets, each sheet is applied to a different surface of the insulating layer, wherein each sheet has the same size as the surface to be covered. In addition, in such an embodiment, the insulating layer can be in the form of a flat sheet. According to certain embodiments, the board of the present invention is characterized in that a first flat layer or flat sheet of mortar (especially cementitious mortar) is firmly attached to one surface of the insulating layer (preferably, a flat sheet of the insulating layer) and completely covers the surface of the insulating layer. Optionally, in such an embodiment, a second flat sheet of mortar, especially cementitious mortar, is firmly attached to the second surface of the insulating layer, especially the flat sheet of the insulating layer, and completely covers said second surface of the insulating layer. Preferably, the first and second surfaces so covered are opposite sides of the insulating layer. Further preferably, the insulating layer is in the form of a flat sheet. Very preferably, in such an embodiment, the width and length of the mortar, especially cementitious mortar, layer or sheet are equal to the width and length of the insulating layer.
[0157] The board according to the invention comprising an insulating layer formed of hardened inorganic foam and at least one structural reinforcement element being a cementitious mortar has particularly good fire resistance. The board according to the invention comprising an insulating layer formed of hardened inorganic foam and at least one structural reinforcement element being a cementitious mortar has in particular an excellent balance of insulating properties (in particular thermal and / or acoustic insulation properties), fire resistance properties and strength (in particular compressive and / or flexural strength).
[0158] The panel of the present invention may have any form or shape as described above. According to an embodiment, the panel of the present invention is in the form of a rectangular sheet with a total thickness between 0.2-50 cm, preferably between 0.5-25 cm, more preferably between 5-25 cm. The total thickness of the panel of the present invention relates to the combined thickness of the insulating layer formed by the hardened inorganic foam plus the thickness of any, at least one structural reinforcement element. In particular, the thickness of the insulating layer formed by the hardened inorganic foam can be adjusted to provide the desired insulation properties, in particular thermal insulation and / or sound insulation and / or fire resistance, and the thickness of at least one structural reinforcement element can be adjusted to provide the desired strength, in particular compression and / or bending strength. It may be preferred that the thickness of the insulating layer formed by the hardened inorganic foam and the thickness of at least one reinforcement element are different.
[0159] According to an embodiment, the panel of the invention comprises (i) an insulating layer formed of hardened inorganic foam with a density in the range of 50-200 g / l, said layer having a thickness of 5-20 cm, and b) and at least one structural reinforcing element firmly connected to at least one surface of said hardened inorganic foam and having a thickness between 2-5 cm, said structural reinforcing element being formed of hardened cementitious mortar, the density of said hardened cementitious mortar being at least 1.5 times higher, preferably at least 2 times higher, preferably at least 5 times higher than the density of the hardened inorganic foam.
[0160] All embodiments described above also relate to these embodiments.
[0161] According to a second aspect, the invention relates to a method of manufacturing a panel according to the invention.
[0162] According to an embodiment, the method comprises the following steps:
[0163] (i) providing inorganic foam,
[0164] (ii) provide cementitious mortar,
[0165] (iii) bringing the inorganic foam and the cementitious mortar into close contact while still in an uncured state, and
[0166] (iii) Hardening the inorganic foam and cementitious mortar assembly.
[0167] In step iii), a mortar layer, preferably a cementitious mortar, may be applied to at least one surface of the inorganic foam, while the inorganic foam is preferably still wet. In addition, an additional primer or binder material may be applied to the inorganic foam before applying the cementitious mortar layer.
[0168] In step iii), the inorganic foam may likewise be applied to at least one layer of cementitious mortar, while the cementitious mortar is preferably still wet.Additionally, an additional primer or adhesive material may be applied to the cementitious mortar before applying the inorganic foam layer.
[0169] According to an embodiment, the method of the present invention further comprises the following steps:
[0170] a) optionally filling the mould with wet cementitious mortar,
[0171] b) placing the inorganic foam into a mould, if any, which is the same mould as used in a), and
[0172] c) Apply cementitious mortar on top of the inorganic foam in the same mould.
[0173] According to other embodiments, the method of the present invention further comprises the following steps:
[0174] a) optionally extruding a wet cementitious mortar layer,
[0175] b) extruding a layer of said inorganic foam, or if step a) is present, extruding a layer of said inorganic foam in a wet state on top of said cementitious mortar, and
[0176] c) Extruding a cementitious mortar layer on top of the inorganic foam.
[0177] The method of the present invention can be a co-extrusion method. Thus, the mortar layer, preferably the cementitious mortar layer, can be co-extruded with the inorganic foam material. Alternatively, the inorganic foam material can also be extruded onto the mortar surface. Another way is the layered deposition of the inorganic foam material and the mortar layer, preferably the cementitious mortar layer.
[0178] However, in particular in the case where the density of the inorganic foam and the cementitious mortar in the wet state is largely different, for example, in the case where the density of the cementitious mortar in the wet state is 2 or 5 times higher than the density of the inorganic foam in the wet state, applying the cementitious mortar on top of the inorganic foam may result in the cementitious mortar sinking into the inorganic foam and / or the foam layer collapsing. In this case, therefore, it may be preferable to harden the inorganic foam at least to some extent before applying the cementitious mortar on top. The term "harden at least to some extent" refers to a hardening time that is sufficient for the inorganic foam to develop sufficient mechanical strength to bear the weight of the cementitious mortar.
[0179] According to some embodiments, the cementitious mortar is applied to the inorganic foam only after the inorganic foam has hardened at least to some extent.
[0180] Therefore, according to an embodiment, the method for producing the panel of the present invention comprises the following steps:
[0181] (i) providing inorganic foam,
[0182] (ii) provide cementitious mortar,
[0183] (iii) when the inorganic foam has hardened to at least some extent and the cementitious mortar is still wet, bringing the inorganic foam and the cementitious mortar into intimate contact, and
[0184] (iii) Hardening of the inorganic foam and cementitious mortar components.
[0185] According to some other embodiments, the inorganic foam is applied to the cementitious mortar only after the cementitious mortar has hardened at least to some extent.
[0186] Therefore, according to an embodiment, the method for producing the panel of the present invention comprises the following steps:
[0187] (i) providing inorganic foam,
[0188] (ii) provide cementitious mortar,
[0189] (iii) when the cementitious mortar has hardened to at least some extent and the inorganic foam is still wet, bringing the inorganic foam and the cementitious mortar into intimate contact, and
[0190] (iii) Hardening of the inorganic foam and cementitious mortar components.
[0191] The mortar (preferably cementitious mortar), inorganic foam and insulating layer are as described above. Therefore, all embodiments and preferred features as described above also apply to this aspect of the invention.
[0192] Very preferably, hardening is carried out at 5-50° C. and a pressure of 1 atm. Hardening at higher temperatures and / or pressures, for example in an autoclave, is not preferred.
[0193] Particularly, according to an embodiment, in the method of the present invention, the chemical compositions of the inorganic foam and the cementitious mortar are the same, and the cementitious mortar has a higher density than that of the inorganic foam.
[0194] A particular advantage is that such panels can be easily recycled.
[0195] The method of making the panels of the invention can be performed at a given site. Thus, the panels of the invention can be made on site, such as at a building site or at a site where a system using such panels is manufactured. Likewise, the method of making the panels of the invention can be performed off-site. Thus, the panels of the invention can also be prefabricated and transported to a construction site for installation, or transported to a site where the panels are subsequently used to manufacture other systems.
[0196] In another aspect, the invention relates to the use of a board as described above or obtained by a process as described above as a thermal and / or acoustic and / or fire protection board or as part of a thermal insulation system or as part of a acoustic insulation system or as part of a fire protection system.
[0197] According to an embodiment, the panel has a thermal conductivity of 0.02 to 0.15 W / m·K, preferably 0.03 to 0.07 W / m·K, measured as described in standard DIN EN 12664: 2001, a density of not more than 500 g / l, preferably not more than 350 g / l, more preferably not more than 250 g / l, even more preferably not more than 200 g / l, for example 25-250 g / l, preferably 35-150 g / l, measured as described above, and an impact resistance according to EOTA EAD 040083-00-0404 (2019) Class I or Class II. In an alternative, the mortar has a compressive strength of not less than 70 kPa, preferably not less than 100 kPa, more preferably not less than 300 kPa, measured according to DIN EN 826: 2013.
[0198] According to an embodiment, the thermal and / or acoustic insulation board of the invention has fire resistance properties or can be used as a fire barrier. Fire resistance properties are present in this context when the requirements of at least one of the following standards are met: UL 790, UL 1256, FM Approvals 4880, FM Approvals 4882, ASTM E 84, ASTM E 108, EN 13501-1. Very preferably, the board of the invention complies with class A1 or A2 according to standard EN 13501:2019-05.
[0199] In another aspect, the invention relates to the use of a panel as described above or a panel obtained by a method as described above as a cover panel and / or as a passive fire protection barrier.
[0200] In particular, the cover board in the sense of the present invention can be used for roofing applications. The cover board can be applied under the roof membrane to provide a fire barrier, add additional thermal and / or acoustic insulation, and / or support and reduce stress on the roof membrane.
[0201] According to an embodiment, the panel has a thermal conductivity of 0.02 to 0.15 W / m·K, preferably 0.03 to 0.07 W / m·K, measured as described in standard DIN EN 12664: 2001, a density of not more than 500 g / l, preferably not more than 350 g / l, more preferably not more than 250 g / l, even more preferably not more than 200 g / l, for example 25-250 g / l, preferably 35-150 g / l, measured as described above, and an impact resistance according to EOTA EAD 040083-00-0404 (2019) Class I or Class II. In an alternative, the mortar has a compressive strength of not less than 70 kPa, preferably not less than 100 kPa, more preferably not less than 300 kPa, measured according to DIN EN 826: 2013.
[0202] According to an embodiment, the cover board of the invention has fire resistance properties or can be used as a passive fire barrier. Fire resistance properties are present in this context when the requirements of at least one of the following standards are met: UL 790, UL 1256, FM Approvals 4880, FM Approvals 4882, ASTM E 84, ASTM E 108, EN 13501-1. Very preferably, the board of the invention complies with class A1 or A2 according to standard EN 13501-1:20 19. BRIEF DESCRIPTION OF THE DRAWINGS
[0203] Figure 1a : shows an insulation panel according to the invention. Figure 1a In the embodiment shown, the panel (1) comprises an insulating layer (2) formed of hardened inorganic foam and at least one structural reinforcement element (3) firmly connected to one surface (4) of said hardened inorganic foam (2).
[0204] Figure 1b : Shows an insulation panel according to the invention. Figure 1b In the embodiment shown, the panel (1) comprises a first structural reinforcement element (3a) firmly attached to a first surface (4a) of the insulation layer (2) and a second reinforcement element (3b) firmly attached to a second surface (4b) of the insulation layer (2).
[0205] Figure 1c : shows an insulation panel according to the invention. Figure 1c In the embodiment shown, the panel (1) comprises two insulating layers (2a, 2b) formed of hardened inorganic foam and at least one structural reinforcement element (3), which is firmly attached to a first surface (4a) of the first insulating layer (2a) and further firmly attached to a second surface (4b) of the second insulating layer (2b).
[0206] Figure 2 : is a graph showing the dependence of the impact area diameter and the total panel density. Figure 2 In the graph, the black dots and black line correspond to the curves of impact resistance versus total panel density (the black dots represent the measured values in Table 1 in the experimental part, and the black line represents the best curve fitted to these results). The five black crosses correspond to the impact area diameters of panels 2-1, 2-3, 3-2, 3-3, and 3-4 in the experimental part. The three black triangles correspond to the impact area diameters of panels 2-2, 2-4, and 3-1 in the experimental part.
[0207] The numbers in the figure have the following meanings:
[0208] 1 – Panel 2 – Insulation layer 2a – First insulation layer 2b – Second insulation layer 3 – Structural reinforcement element 3a – First structural reinforcement element 3b – Second structural reinforcement element 4 – Surface 4a – First surface 4b – Second surface Example
[0209] For the preparation of the foamed mineral binder composition, a device of the "Foamed Concrete Laboratory Mixer - SBL" type from GERTEC Maschinen- und Anlagenbau GmbH (Germany) was used. Thereby, an aqueous foam with a predetermined density was prepared in a first container, and a cement paste was prepared separately in a second container. Subsequently, the aqueous foam and the cement paste were driven by pressurized air through the static mixing unit of the device to obtain the foamed mineral binder composition, i.e. the foamed cement composition. Thereby, the target foam density of the foamed cement composition was adjusted by the air pressure.
[0210] The cement paste was prepared from 64w% CEMI type Portland cement, 25.6w% water, 6.4w% of a synthetic organic polymer SP (ethylene-vinyl acetate copolymer with a Tg of 16°C and stabilized with PVA), 3.8w% of a polyurethane polymer (used as a dispersion in water, 3.8w% relates to the polymer content).
[0211] Aqueous foam was prepared from 97 w% water and 3 w% of a mixture of anionic and nonionic surfactants.
[0212] The production of foam was started with a Gertec SBL equipment and the foam was produced by placing a layer with a thickness of 14 cm and a target density of 100-200 g / l into a mould. The surface of the layer was levelled and the corresponding foam was placed at 23°C / 50% rh. After 1 day, the foam was demoulded and left to cure for a total of 28 days. The details of the foam thus produced are reported in Table 1 below.
[0213] Alternatively, panels are produced as follows:
[0214] A first layer of foam with a thickness of 2-4 cm and a target density of 250 and 500 g / l, respectively, was placed in the mould. This first layer was levelled and then a second layer of foam with a thickness of 10-12 cm and a target density of 100 g / l was applied directly on top of the first layer in the mould. This second layer was levelled and the corresponding panels were placed at 23°C / 50% rh. After 1 day, the panels were demoulded and left to cure for a total of 28 days.
[0215] The details of the panels thus produced are reported in Table 2 below. Panels of type I have a first layer 4 cm thick and with a density of 250 g / l and a second layer 10 cm thick and with a density of 100 g / l. Panels of type II have a first layer 2 cm thick and with a density of 500 g / l and a second layer 12 cm thick and with a density of 100 g / l.
[0216] The obtained foams and panels were tested for impact resistance following a procedure similar to the method described in EN ISO 7892 and EOTA EAD 040083-00-0404 (2019). For this test, a steel ball with a diameter of 74 mm and a weight of 644 g was dropped from a height of 47.5 cm onto the corresponding surface of the hardened inorganic foam or panel as indicated in Table 1 or 2 below. The diameter of the impact area is reported in Tables 1 and 2 below.
[0217] Table 1: Impact resistance of hardened inorganic foams
[0218] Table 2: Panel impact resistance
[0219] From the results in Table 1 above, it is clear that the impact resistance increases with the density of the impacted material. This increase is not linear, as the upper limit of the impact resistance is reached with increasing density (see Figure 2 black line in the figure).
[0220] The results of Table 2 above show that the panels according to the invention have sufficiently high impact resistance and are therefore suitable, for example, as thermal insulation panels for facade applications with class II impact resistance according to EOTA EAD 040083-00-0404 (2019). Compared to pure foam with the same total density, the type I panel with a total density of 143 g / L has a lower impact zone diameter and therefore has higher impact resistance on the high-density side. This is also true for the type II panel with a total density of 157 g / L.
[0221] In addition, panels were produced in the same manner and with the same materials as described above, but with the thickness and density of the layers as shown in Table 3 below. The impact resistance of the panels was measured as described above. Therefore, the second layer was always impacted. The thermal conductivity of the individual layer materials was measured according to standard DIN EN 12664: 2001, and the R-value of the panel was calculated therefrom. Each R-value was calculated as the sum of the layer thickness divided by the thermal conductivity of the layer. For example, for panel 3-3, the layer with a density of 100 g / L was measured to have a thermal conductivity of 0.048 W / m·K, and the layer with a density of 250 was measured to have a thermal conductivity of 0.071 W / m·K. Thus, the R-value of panel 3-3 was calculated to be (0.1 / 0.048)+(0.04 / 0.071)=2.6.
[0222] Table 3: Panel impact resistance and R-value
[0223] From the results in Table 3 above, it can be seen that in order to achieve good reinforcement, preferably, the density of the reinforcement layer is at least 150 g / L. It can also be seen that in order to achieve good reinforcement, preferably, the density of the reinforcement layer is at least 1.5 times higher than the density of the inorganic foam. On the other hand, it can be seen that the density of the inorganic foam and / or the reinforcement layer or the overall panel density should not be increased too much, because for a given geometry, this will lead to a decrease in the R-value, thereby resulting in a decrease in thermal insulation performance.
[0224] Enhancements can be made in Figure 2 Seen in. Figure 2 In the graph, the black dots and black line correspond to the curve of the impact resistance vs. density of pure foam (the black dots represent the measured values of Table 1). The five black crosses correspond to the impact zone diameters of panels 2-1, 2-3, 3-2, 3-3, and 3-4 plotted against the total panel density. It can be seen that the black crosses are significantly below the black lines. Therefore, panels 2-1, 2-3, 3-2, 3-3, and 3-4 have higher impact resistance than pure foam of comparable total density and are therefore enhanced. On the other hand, Figure 2 Plates 2-2, 2-4 and 3-1 indicated by the middle black triangles did not show improved enhancement.
Claims
1. A panel (1) comprising a thermal insulation layer (2) formed of a hardened inorganic foam and at least one structural reinforcement element (3) firmly attached to at least one surface (4) of the hardened inorganic foam (2), wherein the at least one structural reinforcement element (3) is a hardened mortar, preferably a hardened cementitious mortar.
2. The panel (1) according to claim 1, characterized in that A first structural reinforcement element (3a) is firmly attached to a first surface (4a) of the insulation layer (2), and a second reinforcement element (3b) is firmly attached to a second surface (4b) of the insulation layer (2).
3. The plate (1) according to claim 2, characterized in that The first surface (4a) and the second surface (4b) of the isolation layer (2) are opposite surfaces.
4. Panel (1) according to at least one of the preceding claims, characterized in that The hardened inorganic foam comprises: a) at least one cured inorganic binder B, b) at least one surfactant S and / or particles N, and c) optionally at least one synthetic organic polymer SP.
5. Panel (1) according to at least one of the preceding claims, characterized in that The reinforcing element (3) is a hardened cementitious mortar obtained from (in each case relative to the total dry weight of the composition) a) 10-90w%, preferably 15-65w%, more preferably 30-55w% of at least one inorganic binder B, b) 0-80w%, preferably 25-75w%, more preferably 35-60w% of aggregates, especially sand, c) 0.01-10w% of other additives, and d) water.
6. The panel (1) according to at least one of claims 1 to 4, characterized in that The insulating layer (2) and each structural reinforcement element (3) formed of hardened inorganic foam are almost identical in chemical composition or have substantially the same chemical composition, and each structural reinforcement element (3) has a higher density than the insulating layer (2).
7. Panel (1) according to at least one of the preceding claims, characterized in that The density of the isolation layer (2) is not greater than 500 g / l, preferably not greater than 350 g / l, more preferably not greater than 250 g / l, even more preferably not greater than 200 g / l, for example 25-250 g / l, preferably 35-150 g / l.
8. Panel (1) according to at least one of the preceding claims, characterized in that The density of the at least one structural reinforcement element (3) is at least 1.5 times, preferably at least 2.5 times, the density of the insulation layer (2).
9. Panel (1) according to at least one of the preceding claims, characterized in that The total density of the panel (1) is not higher than 500 g / l, in particular not higher than 300 g / l, preferably in the range of 110-500 g / l, more preferably in the range of 160-250 g / l.
10. A panel (1) according to any one of the preceding claims, characterised in that The insulating layer (2) has a thermal conductivity between 0.02 and 0.15 W / m·K, preferably between 0.03 and 0.07 W / m·K.
11. A method of manufacturing a panel (1) according to any one of claims 1 to 10, the method comprising the steps of: (i) providing an inorganic foam, (ii) providing a cementitious mortar, (iii) bringing the inorganic foam and the cementitious mortar into intimate contact while still in an uncured state, and (iv) hardening the assembly of the inorganic foam and the cementitious mortar.
12. A method for manufacturing a panel (1) according to claim 11, characterized in that: The method further comprises the following steps: a) optionally filling the mould with wet cementitious mortar, b) placing the inorganic foam into a mould, if any, which is the same mould as used in a) and c) Apply cementitious mortar on top of the inorganic foam, preferably in the same mould, if present.
13. A method for manufacturing a panel (1) according to claim 11, characterized in that: The method further comprises the following steps: a) optionally extruding a wet cementitious mortar layer, b) extruding a layer of said inorganic foam, or if step a) is present, extruding a layer of said inorganic foam in a wet state on top of said cementitious mortar, and c) Extruding a cementitious mortar layer on top of the inorganic foam.
14. A method for manufacturing a panel (1) according to any one of claims 11 to 13, characterized in that: The inorganic foam and the cementitious mortar have the same chemical composition, and the cementitious mortar has a higher density than the inorganic foam.
15. Use of a panel (1) according to any one of claims 1 to 10 or a panel (1) manufactured according to any one of claims 11 to 14 as a thermal and / or acoustic insulation board and / or a fire protection board, or as part of a thermal insulation system, or as part of a acoustic insulation system, or as part of a fire protection system.
16. Use of a panel (1) according to any one of claims 1 to 10 or a panel (1) produced by a method according to any one of claims 11 to 14 as a cover panel and / or as a passive fire protection barrier.
